Preventing the politicisation of corruption crime law enforcement based on local wisdom - Erma Rusdiana; Nurus Zaman; Lindra Darnela; Uswatun Hasanah (Legality : Jurnal Ilmiah Hukum, 2025)
This study focuses on the phenomenon of politicised law enforcement in corruption cases during election years, where legal actions are suspected of being used as political tools to weaken opponents and maintain power. Consequently, law enforcement is perceived as "by order" and heavily influenced by vested interests. This entanglement between politics and law is attributed to a lack of integrity and moral values among the involved actors, further undermining democratic practices and justice. This study analyses how the politicisation of law occurs in the electoral context and its impact on law enforcement and proposes a solution to prevent the politicisation of corruption in law enforcement through local wisdom-based approaches. This research employs a socio-legal method, analysing secondary data from various corruption cases exposed ahead of the 2014, 2019, and 2024 elections. This analysis includes literature reviews, investigative reports, and data from law enforcement agencies. Findings indicate a consistent pattern where corruption in law enforcement involving public officials tends to intensify as elections approach, suggesting efforts to politicise the law. Such politicisation negatively impacts genuine anti-corruption efforts by casting the law as a political instrument rather than a means of upholding justice, thus degrading the dignity of law enforcement and affecting public perception. Taking Malaysia as an example in successfully improving its Corruption Perceptions Index (CPI), this study underscores the importance of strengthening integrity by instilling moral values rooted in local wisdom, such as "Hasta Brata" and the "nine anti-corruption values." These efforts are essential to establishing dignified democratic practices and fair law enforcement that are free from corruption, collusion, and nepotism.